A modified flower pollen-based photothermocatalytic process for enhanced solar water disinfection: Photoelectric effect and bactericidal mechanisms. (15th June 2022) - Xia, Dehua; Chen, Qi; Jiao, Yimu; Lian, Qiyu; Sun, Mingzhe; He, Chun; Shang, Jin; Wang, Tianqi
Highlights: Te-TRP created the synergies between photothermal conversion and photocatalysis. The solar/Te-TRP system showed excellent inactivation towards 3 types of bacteria. Efficient SODIS was demonstrated using a dedicatedly designed flow-through reactor. 1 O2 and ·O2 ¯ were identified to be primary ROS for bacterial inactivation. Damage to cell membrane and enzymes were induced, followed by DNA destruction. Abstract: Solar disinfection (SODIS) is regarded as an affordable and effective point-of-use (POU) water disinfection treatment urgently needed in rural developing world. This work developed an enhanced SODIS scheme that utilized a novel flower pollen-based catalyst (Te-TRP). The bench-scale experiments demonstrated 100% photothermocatalytic inactivation of approximately 7-log E. coli K-12, Spingopyxis sp. BM1-1, or S. aureus bacterium by Te-TRP within 40–60 min. Moving toward practical device design, we constructed a flow-through reactor and demonstrated the outstanding water disinfection performance of Te-TRP. The in-depth mechanistic study revealed the synergetic effect between photocatalysis and photothermal conversion and identified the bacterial inactivation pathway. 1 O2 and ·O2 ¯ were verified to be the dominant reactive oxygen species involved in the bacterial inactivation. The damage to bacterial cells caused by photothermocatalytic reactions was systematically investigated, demonstrating the cell membrane destruction, the loss of enzyme activity, the increased cell membrane permeability, and the complete inactivation of bacteria without the viable but nonculturable state cells. This work not only affords a facile approach to preparing biomaterial-based catalysts capable of efficient photothermocatalytic bacterial inactivation, but also proposes a prototype of POU water treatment, opening up an avenue for sustainable environmental remediation. Graphical abstract: This study developed a biomass-based system for affordable and effective photothermocatalytic water disinfection and revealed the underlying mechanisms. Image, graphical abstract